If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + 7) = 9 Reorder the terms: -2(7 + x) = 9 (7 * -2 + x * -2) = 9 (-14 + -2x) = 9 Solving -14 + -2x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + -2x = 9 + 14 Combine like terms: -14 + 14 = 0 0 + -2x = 9 + 14 -2x = 9 + 14 Combine like terms: 9 + 14 = 23 -2x = 23 Divide each side by '-2'. x = -11.5 Simplifying x = -11.5
| -25=-59 | | r+7+6r=6r | | 195=15k | | 3x+4*6= | | 49-23x=6x-29 | | 3[5-(-5x-1)]=135+42 | | 2ln(4x)-1=6 | | 29-3+10=x-3 | | 8x^2-5=-18x | | 6n+5+4=15 | | 20k-30=17k | | (-6c)2= | | (32/x^3)-2x=0 | | -18=6(p-2) | | (14x^6-10x^5)/2x^2 | | 3x-(-4)=14-66 | | 14=7x+6-3x | | x^2+6x+y^2+10y=8 | | (6x^3-2x^2+6x-3)-(-9x^3-8x^2-4x+3)= | | -5(v+4)+2v+52=7v+7 | | -5(-4-6r)-5=37+8r | | 12•4/3 | | x+32=x+4 | | 4n+1+10=4 | | .07x+.04(x-1100)=154 | | -14=10y | | 4xy+2y=0 | | 0=.97+0t-4.9t^2 | | -3m-5=5m-13 | | 7c=-4c+66 | | -.666x+3=2 | | 7n-6n=5(n+8)-(1-9n) |